Simultaneous TKA and Revision of Post-ORIF Patellar Non-union with Bone Grafting: A Case Report - Hiroko Sakamoto; Masaki Nagashima; Ryo Sasaki; Kentaro Tanaka; Mitsuru Yagi (Journal of Orthopaedic Case Reports)
Introduction: Treatment of advanced knee osteoarthritis (OA) with periarticular fractures is challenging, particularly when accompanied by non-union of patellar fractures. In the elderly, multiple surgeries pose disadvantages because they increase the anesthetic risk and the incidence of perioperative complications and prolong the time required for functional recovery. We report a case of advanced knee OA with non-union of a patellar fracture after open reduction and internal fixation (ORIF) that was treated with one-stage total knee arthroplasty (TKA) together with bone grafting. Case Report: An 85-year-old female with advanced OA of the left knee presented with the treatment of non-union of a left patellar fracture following ORIF. Conservative treatment using low-intensity pulsed ultrasound and teriparatide for 1 year proved ineffective, prompting us to perform simultaneous TKA and ORIF of the patellar non-union. One year postoperatively, the patient achieved a favorable outcome. Conclusion: We performed simultaneous left TKA and ORIF with bone grafting in a patient with knee OA and non-union of a patellar fracture. This procedure allowed the bone resected during TKA to be used for bone grafting at the pseudarthrosis site.